PROVINCIAL-LEVEL DETERMINANTS OF ENERGY INTENSITY: THE INTERPLAY OF ENVIRONMENT GOVERNANCE INDEX, FIRM CHARACTERISTICS, AND REGIONAL DEVELOPMENT - Nguyen Hoang Long; Chu Thi Mai Anh; Phan Huong Giang (Graduate Program of Universitas Tarumanagara, 2024)
Vietnam's rapid economic growth has raised concerns about energy consumption. This study investigates factors influencing enterprise energy use by analyzing data from 2018 to 2020. It examines how provincial environmental policies, economic factors, and business characteristics affect energy intensity. The research reveals that strong environmental regulations decrease energy use, but effectiveness varies regionally. Surprisingly, economic activity and a larger workforce are linked to lower energy intensity, potentially reflecting Vietnam's green initiatives and service sector development. Additionally, larger firms and those less reliant on machinery use less energy, while businesses with a bigger labor force consume more. These findings suggest that Vietnam's path to energy efficiency requires a nuanced approach considering both regional policy implementation and the country's unique development trajectory.